آفاق استخدام تقنية النانو تكنولوجي وتطبيقاتها - سميرة عبود (Tishreen University, 2018)
يعرض هذا البحث دراسة مرجعية عن تقنية النانو تكنولوجي((NanoTechnology. يوضّح فيها أشكال المواد النانوية, وطرق تصنيعها, وخصائصها, وتطبيقاتها, ودور تقنيات النانو في الإلكترونيات والضوئيات, كما إنه يشرح إمكانية تصنيع حاسوب من أنابيب الكربون النانوية, ويشرح تقنية البطارية الورقية, والمكثفة الفائقة والعالية السعة, كما إنه يعطي فكرة عن الأجهزة والتقنيات المستخدمة في فحص المواد النانوية, ويعرض البحث تعامل ميكانيك الكم مع الإلكترونيات النانوية, وبالنهاية يعطي فكرة عامة عن أجهزة الكم وعمليات المحاكاة الخاصة بها. This research shows a reference study about the technique of the nanotechnology, kinds of nano materials, methods of its manufacturing, its characteristics, its applications, and the role of nano in electronics and optoelectronic. As well this  research explains the possibility of manufacturing of a computer with carbon nanotubes and the technique of the paper battery and the capacitor with high capacity. This study gives too an overvieo of the devices and the used technique to in vestigate the nano materials.The article  shows too the behavior of the quantum mechanics with the nano electronics. Finally it gives a general overvieo about the quantum devices and their own simulation processes.